New routes in the study of Aviation and Aeronautical English - Tosqui-Lucks, Patrícia; Prado, Malila Carvalho de Almeida (The ESPecialist, 2020)
This text is the Editorial for the second volume of the The Especialist Aviation English special edition. For a contextualization of ICAO[1]Language Proficiency Requirements and for the conceptualization and theoretical background of Aviation and Aeronautical English, please consult the Editorial - Volume 1. There you will also find information about how this special edition was conceived and a list of other compilations related to Aviation English. [1] International Civil Aviation Organization.